Designing an effective student evaluation of teaching (SET) questionnaire for cadaveric dissection - Chaudhuri, Joydeep D.; Venugopal Rao, B. (International Journal of Research in Medical Sciences, 2017)
Recent changes in curriculum have seen a curtailment in the time devoted to the teaching of gross anatomy, one of the most integral components of medical education. This has resulted in the reduction, and in some cases the elimination of cadaveric dissection, most significantly due to the huge amount of resources involved in conducting a cadaveric dissection program. Nevertheless, cadaveric dissection still comprises a significant part of the time devoted to the teaching of gross anatomy. Hence it is of paramount importance that maximum benefit be derived from cadaveric dissections since it offers unique advantages, most significant being the appreciation of the three-dimensional concepts of body organization. The key part of effective anatomy teaching using cadaveric dissection is having the best instructors for this task. While student evaluation of teaching (SET) questionnaires have been used to evaluate instructor proficiency in lecture classes, there is no SET questionnaire that has been specifically designed for the assessment of instructors involved in cadaveric dissection. The aim of this article is to design a questionnaire specifically for the evaluation of the competency of instructors involved in cadaveric dissection, and reinforce the arguments for the continued use of cadaveric dissection in the teaching of anatomy.